An investigation into perceptions of participative management in a Namibian secondary school - Shilima, Christine (Rhodes University, Faculty of Education, Department of Education, 2010)
This study examines the perceptions and experiences of school stakeholders about the practices of participative management in a Namibian Secondary School. Data was collected by using interviews, observation and document analysis. The study revealed that participative management has some benefits for the school such as it promotes democracy in school management, school as an open system, sharing of ideas and skills, teamwork and that ownership and commitment enhance the chances for organization change. Participatory decision making and shared leadership are the practices of PM that emerged from this study. However the school does experience challenges such as lack of knowledge on the practice and potential of PM in school management and leadership, illiteracy among parents that prevent them from participation in management and autocratic management practices from some members in formal leadership. The study suggests that trust, relationships and openness are good interpersonal skills that can help enhance the practices of PM in the school. Other strategies were to sensitize stakeholders on the practices of PM.
Keywords: School management and organization -- Namibia -- Case studies; Educational leadership -- Namibia -- Case studies; Education, Secondary -- Namibia -- Case studies; Education -- Parent participation -- Namibia